Analysing understandings of 'rough sleeping': managing, becoming and being homeless - McCulloch, Daniel Cameron (2015)
This research considers the ways in which the lives of rough sleepers are understood. In doing so, it considers the ways in which rough sleepers are positioned by services, the ways in which rough sleepers account for their own lives, and the ways in which rough sleepers negotiate and manage their day-to-day experiences. Analysing previous literature and policy, the research claims that lives might be better understood using a narrative approach alongside other methods. Therefore, it employs methods of life mapping and auto-photography with rough sleepers, alongside participant observation and semi-structured interviews with service providers. These methods aided the understanding of the ways in which each group understands rough sleepers’ lives. The research finds that in contrast to policy and service provider discourses, which often focus on deficits, discourses of poor decision making in ideas of causation, and dichotomies of deservingness, rough sleepers’ own accounts focus on the importance of context to develop an understanding of the importance of key life events. Furthermore, the research suggests that understandings of rough sleepers’ lives presented in policy and service provider discourses which see these lives as ‘chaotic’, ‘off track’ and ‘failed’ are in stark contrast to rough sleepers own accounts, which entail elements of order, success, and aspirations. In considering these alternative approaches to understanding the lives of rough sleepers, the study proposes that narrative approaches to engaging with rough sleepers, which recognise the agency that rough sleepers have, could provide a way to better understand the ways in which rough sleepers understand their own lives